1975
DOI: 10.1071/ar9750423
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of semiarid grasses. I. The influence of phosphorus supply on growth and phosphorus absorption

Abstract: Experiments were carried out under controlled conditions to investigate the physiological bases for species differences in yield and nutrient responses to variations in phosphorus supply. Buffel grass (Cenchrus ciliaris), and to a less extent Mitchell grass (Astrebla elymoides), showed a much larger yield response to increasing phosphorus supply than mulga grass (Thyridolepis mitchelliana). Mitchell and mulga grasses had much lower relative growth rates than buffel grass. Mulga grass required a lower external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
2

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(59 citation statements)
references
References 14 publications
6
50
1
2
Order By: Relevance
“…This result is in agreement with the findings of Brewster, Bhat and Nye (1975a, b) who suggested that this could be caused by inter-root competition for phosphate, which becomes more serious with time as roots become clumped at the sides and bottoms of the pots, and/or a general change in root absorbing properties with increasing physiological age of the plant. The latter has been demonstrated in solution culture with constant phosphate concentration (Christie and Moorby, 1975;Brewster et al, 1975a). Inflows to root systems infected with LAM, YV and BR endophytes were increased above those to control roots even at low percent infections.…”
Section: Discussionmentioning
confidence: 91%
“…This result is in agreement with the findings of Brewster, Bhat and Nye (1975a, b) who suggested that this could be caused by inter-root competition for phosphate, which becomes more serious with time as roots become clumped at the sides and bottoms of the pots, and/or a general change in root absorbing properties with increasing physiological age of the plant. The latter has been demonstrated in solution culture with constant phosphate concentration (Christie and Moorby, 1975;Brewster et al, 1975a). Inflows to root systems infected with LAM, YV and BR endophytes were increased above those to control roots even at low percent infections.…”
Section: Discussionmentioning
confidence: 91%
“…Seeds, for example, often have lower PUE than stems because seeds require more P to produce a given d. wt than do stems. Variation in PUE also occurs among plant species (Christie & Moorby, 1975 ;Haynes et al, 1991), and as a consequence of *Author for correspondence (fax j1 814 863 6139 ; e-mail rxk13!psu.edu). variation in P availability and mycorrhizal colonization (Chapin, 1980 ;Haynes et al, 1991 ;Koide, 1991).…”
Section: mentioning
confidence: 99%
“…Growth analysis, which can be used to describe some of these, has been used in attempts to understand differences in response to phosphorus (P) among species (Barrow 1975(Barrow , 1977 Biddiscombe et aI. 1969; Christie & Moorby 1975; Keay et aI. 1970;White 1972White , 1973 and to develop a model for P uptake and plant growth (Nye et aI.…”
Section: Introductionmentioning
confidence: 99%